HIV-1 associated neuroinflammation : effects of two complimentary medicines illustrated in an in vitro model of the blood-brain barrier - Africa, Luan Dane (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2014.